Analisis Perbedaan Pendapatan Usaha Tani Jagung Kuning dengan Usahatani Kacang Tanah di Desa Mokupa Kabupaten Kolaka - Iksanudin Iksanudin; Muhammad Nur; Nurcayah Nurcayah (Fakultas Pertanian Universitas Muhammadiyah kendari, 2022)
The income difference between yellow corn farming and peanut farming. This research is aimed to know the difference of income between yellow corn farming and peanut farming in Mokupa Village, Lambandia Sub-district, Kolaka District. The population of this study is all farmers who cultivate yellow corn and peanut in Mokupa Village, Lambandia Subdistrict with sample determination technique done by census. To know the difference of income between yellow corn farming and farming of peanut used earn income analysis and income comparison analysis. The result of research indicate that there is between yellow corn farming and peanut farming. In each growing season, the average income of yellow corn farmers is Rp. 7.546.993 while peanut farmers Rp. 7.526.147 based on t test analysis showed that with 95% confidence level t count = 0.03 and ttabel 1.693, so H0 rejected and statistically there is difference of income of yellow corn farming with peanut farming.